2001
DOI: 10.1104/pp.125.4.1788
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Floral Meristem Identity Genes. Analysis ofLolium temulentum Genes Related to APETALA1 andLEAFY of Arabidopsis

Abstract: Flowering (inflorescence formation) of the grass Lolium temulentum is strictly regulated, occurring rapidly on exposure to a single long day (LD). During floral induction, L. temulentum differs significantly from dicot species such as Arabidopsis in the expression, at the shoot apex, of two APETALA1 (AP1)-like genes, LtMADS1 and LtMADS2, and of L. temulentum LEAFY (LtLFY). As shown by in situ hybridization, LtMADS1 and LtMADS2 are expressed in the vegetative shoot apical meristem, but expression increases stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 62 publications
9
102
1
4
Order By: Relevance
“…Entretanto, este homólogo de LFY não é expresso no meristema vegetativo propriamente dito de E. grandis, diferentemente de H. suaveolens. Já em outra espécie tipicamente invasora, Lolium temulentum, LtLFY não é expresso em ápices vegetativos e somente é detectado tardiamente (cerca de 12 dias após indução floral de dias longos) nos meristemas e primórdios florais (Gocal et al 2001), contrastando assim em vários aspectos com o padrão de expressão do ortólogo putativo de LFY em H. suaveolens. Contudo, comparações entre os padrões de expressão de homólogos de LFY nestas duas espécies invasoras não são muito informativas, devido principalmente às diferenças nos ciclos fotoperiódicos indutivos e nas respectivas classes das espécies em questão, dicotiledôneas (H. suaveolens) e monocotiledôneas (Lolium temulentum).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Entretanto, este homólogo de LFY não é expresso no meristema vegetativo propriamente dito de E. grandis, diferentemente de H. suaveolens. Já em outra espécie tipicamente invasora, Lolium temulentum, LtLFY não é expresso em ápices vegetativos e somente é detectado tardiamente (cerca de 12 dias após indução floral de dias longos) nos meristemas e primórdios florais (Gocal et al 2001), contrastando assim em vários aspectos com o padrão de expressão do ortólogo putativo de LFY em H. suaveolens. Contudo, comparações entre os padrões de expressão de homólogos de LFY nestas duas espécies invasoras não são muito informativas, devido principalmente às diferenças nos ciclos fotoperiódicos indutivos e nas respectivas classes das espécies em questão, dicotiledôneas (H. suaveolens) e monocotiledôneas (Lolium temulentum).…”
Section: Resultsunclassified
“…Contudo, comparações entre os padrões de expressão de homólogos de LFY nestas duas espécies invasoras não são muito informativas, devido principalmente às diferenças nos ciclos fotoperiódicos indutivos e nas respectivas classes das espécies em questão, dicotiledôneas (H. suaveolens) e monocotiledôneas (Lolium temulentum). O papel de genes relacionados a LFY é menos compreendido em monocotiledôneas do que em dicotiledôneas, e aparentemente a hierarquia da regulação floral envolvendo genes de identidade do meristema descrita em dicotiledôneas pode não ser conservada em monocotiledôneas (Gocal et al 2001). A divergência funcional dos ortólogos de FLO/LFY em monocotiledôneas pode ser notada também em outras espécies, como no trigo, onde o gene WFL está associado com o desenvolvimento das espiguetas ao invés da especificação de identidade do meristema floral devido Tabela 1.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Functional domains of MADS box genes including DEF are well characterized (e.g., Reichman and Meyerowitz 1997) including the MADS, I, K, and C-terminus regions; for analyses we treated the DNA binding domain (MADS) as distinct from other regions (I, K, and C-terminus). Functional domains of FLO are not as well characterized, but FLO is a transcription factor (Coen et al 1990) and the highly conserved C-terminus region of the Arabidopsis thaliana ortholog LFY is reported to bind DNA (Gocal et al 2001) and has been suggested to constitute the DNA binding domain (Bomblies et al 2003). For our analyses we treated the putative DNA binding domain as distinct from the N-terminus region of FLO.…”
Section: Codon Substitution Modelsmentioning
confidence: 99%